Quantification of non-homogeneous interval uncertainty based on scatter in modal properties. (2017) - Faes, Matthias; Moens, David
Abstract: The objective of this work is to develop and validate a methodology for the identification of intra-variability based on the Interval Field concept, with a specific focus on dynamic FE models. The principal idea is to find a solution to an inverse problem, where the variability on the output side of the model (i.e., the eigenfrequencies) is known from measurement data, but the spatial uncertainty on the input parameters is unknown. Specifically, focus is placed on the identification of the topology of the non-homogeneous interval uncertainty, modelled as an interval field. This identification is performed by comparing the gradients of the halfspaces bounding the uncertain set resulting from the propagation of the interval field and the measurement data set. It is shown that an accurate identification is feasible following the proposed methodology.